An energy‐biochar chain involving biomass gasification and rice cultivation in Northern Italy. Issue 2 (21st December 2012) - Lugato, Emanuele; Vaccari, Francesco P.; Genesio, Lorenzo; Baronti, Silvia; Pozzi, Alessandro; Rack, Mireille; Woods, Jeremy; Simonetti, Gianluca; Montanarella, Luca; Miglietta, Franco
Abstract The competing demand for food and bioenergy requires new solutions for the agricultural sector as, for instance, the coupling of energy production from gasification technology and the application of the resulting biochar as soil amendment. A prerequisite for the implementation of this strategy is the scale‐specific assessment of both the energetic performance and of the impacts in terms of greenhouse gases (GHG) emission and crop responses. This study considered the gasification process developed by Advanced Gasification Technology (AGT, Italy), which is a fixed‐bed, down‐draft, open core, compact gasifier, having 350 kW of nominal electric capacity (microgeneration); this gasifier uses biomass feedstock deriving from agricultural/forest products and byproducts. In this study, the resulting biochar, derived from conifer wood chips of mountain forestry management in North‐western Italy, was applied to a nearby paddy rice field, located in the largest rice agricultural area of Europe. We performed a Life Cycle Analysis (LCA) adapting the BEAT2 model specifically focusing on the GHG balance of the supply chain, from the forestry management to the field distribution of the resulting biochar. The results indicated that the gasification stage had the highest impact in the supply chain in terms of emissions, but net emissions allocated to biochar were always negative (ranging between −0.54 and −2.1 t CO2e t−1 biochar), hypothesizing two scenarios of 32% and 7.3% biochar mineralization rate in soil, over a time period of 100 years. Finally, biochar had a marginal but positive effect on rice yield, thus increasing the sustainability of this energy‐biochar chain.